1999
DOI: 10.1097/00005537-199912000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser Uvulopalatoplasty on Middle Ear Function

Abstract: No significant effects on middle ear pressures or volumes 3 months after LAUP were demonstrated. A much larger study may, however, arrive at a statistically significant result and further work is warranted. Relevant palatal and tubal anatomy is discussed and a brief review of the relevant literature is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…It was designed to concentrate on the immediate E-tube function after surgery. Most studies have already established that there are immediate and marked MEP reductions that gradually recover [13][14][15][16][17][18][19]. In this study, three weeks after surgery, there were no specific complaints or physical examinations that were suggestive of E-tube dysfunction.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…It was designed to concentrate on the immediate E-tube function after surgery. Most studies have already established that there are immediate and marked MEP reductions that gradually recover [13][14][15][16][17][18][19]. In this study, three weeks after surgery, there were no specific complaints or physical examinations that were suggestive of E-tube dysfunction.…”
Section: Discussionmentioning
confidence: 46%
“…There have also been several clinical studies that investigated the relationship between middle ear function and surgeries that address sleep-disordered breathing including uvulopalatopharyngoplasty, laser-assisted uvulopalatoplasty, Z-palatopharyngoplasty with radiofrequency tongue base ablation, and pillar implants [15][16][17][18][19]. Finkelstein et al [15] described that uvulopalatopharyngoplasty induced noticeable MEP reduction during the first 7 postoperative days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The study examining the impact of Laser Uvulopalatoplasty on Middle Ear Function reported no notable effects on middle ear pressure during the third month following the surgery. 18 In our study, the two-way repeated measures ANOVA revealed a significant main effect of time on ETDQ-7 scores, with a large effect size. However, there was no significant main effect of groups or a significant interaction between time and groups.…”
Section: Palatal Surgeries and Etdsupporting
confidence: 50%
“…A study found that ESP did not improve ET function in the long term and was even associated with temporary ETD during the initial two months following surgery, with a median preoperative apnea‐hypopnea index of 34 events per hour (mean ETDQ score was 16 ± 3.7) 17 . The study examining the impact of Laser Uvulopalatoplasty on Middle Ear Function reported no notable effects on middle ear pressure during the third month following the surgery 18 . In our study, the two‐way repeated measures ANOVA revealed a significant main effect of time on ETDQ‐7 scores, with a large effect size.…”
Section: Discussionmentioning
confidence: 99%